Tunneling‐induced transparency in a chaotic microcavity. Issue 5 (21st June 2013) - Xiao, Yun‐Feng; Jiang, Xue‐Feng; Yang, Qi‐Fan; Wang, Li; Shi, Kebin; Li, Yan; Gong, Qihuang
<x xml:space="preserve">Abstract</x> A new form of induced transparency enabled by dynamical tunneling coupling of continuous chaos and discrete regular modes in a slightly deformed optical microcavity is demonstrated experimentally. An optical beam is focused on the cavity boundary and tuned on resonance with a high‐Q mode, which leads to destructive interference for the excitation of chaotic field and induces a transparency in the transmission. The experimental results are in excellent agreement with a model based on quantum scattering theory. This tunneling‐induced transparency is accompanied by extremely steep normal dispersion, and holds great potential in slow light and enhanced nonlinear interactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>